Kalam Science as a Pillar of Understanding Islamic Creed - Ega Putri Handayani; Maulidani Ulfah; Azhariah Fatia; Lukmanul Hakim (Penerbit Hellow Pustaka, 2025)
This Study examinesthe role of Islamic theology (Ilmu Kalam) as a fundamental pillar in understanding, strengthening, and defending Islamic beliefs (Aqidah) amidst intellectual challenges and deviations in thought. The research employs a library research method with a descriptive approach. Data were collected from books, journal articles, and relevant digital sources. The findings reveal that Ilmu Kalam functions as a tool to fortify faith by combining rational arguments (aqliyah) and textul evidence (naqliyah. Furthermore, ilmu kalam plays a significant role in addressing challenges from greek philosophy, deviant sects such as Mu’tazilah, and modern ideologies like secularism and materialism. Using rational and argumentative methods, ilmu kalam has successfully developed a deeper and more critical understanding os Islamic theological concepts, such as monotheism (Tawhid), the attributes of God, human free will, and divine justice, thus remaining relevant in contemporary intellectual discourse